(untitled) (Journal of actual problems of jurisprudence, 2019)
This article deals with a form of multiple crimes – relapse. The Criminal Code of the Republic of Kazakhstan, which entered into force on 1 January 2015, have undergone significant changes rules on recidivism. The threshold level of recognition of recurrence is significantly increased. Relapse is now comprised only of crimes categorized as serious or very serious. For example, committing a deliberate crime by a small to moderate if he has been convicted of another intentional crime (any category) relapse does not form under any circumstances. Key words: multiple offenses, public danger, imprisonment, violent crimes, especially grave crimes.